Studies on Antimicrobial and Antioxidant Potentials of Pergularia daemia (Forsk.) Chiov. - Jain, S.C.; Pancholi, Boskey; Jain, R. (Asian Journal of Chemistry, 2012)
Pergularia daemia (Forsk.) Chiov., a perennial twining wild herb is known for its varied medicinal properties. In the present study, whole plant material was successively extracted with pet. ether, hexane, dichloromethane, chloroform, ethyl acetate, acetone and methanol, concentrated and investigated for their phytochemical, antibacterial and antioxidant profile. a-, b-amyrin, b-sitosterol, lupeol, lupeol acetate, oleanolic acid, kaempferol and quercetin was isolated. In antibacterial screening, appreciable activities were demonstrated by hexane extract against E. aerogenes (19.66 ± 0.66 mm; MIC 62.5 μg/mL) and ethyl acetate extract against E. coli (19.99 ± 0.67 mm; MIC 31.2 μg/mL) whereas in antifungal screening, acetone extract against A. flavus (16.33 ± 0.87 mm; MIC 125 μg/mL) and chloroform extract against C. albicans (15.66 ± 0.66 mm; MIC 62.5 μg/mL). In antioxidant efficacy, methanol extract demonstrated higher efficacy, i.e. with lowest IC50 value (maximum antioxidant capacity; 0.075 mg/mL with 363.33 ± 3.33 mg AAE/g antioxidant capacity in FRAP assay).